2000
DOI: 10.1034/j.1600-0609.2000.065005317.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gemcitabine (2′,2′‐difluoro‐deoxycytidine) and 2‐chlorodeoxyadenosine on growth of normal and leukemic cellsin vitro

Abstract: The aim of the study was to investigate the influence of gemcitabine (2',2'-difluorodeoxycytidine, dFdC) used alone and in combination with 2-chlorodeoxyadenosine (2-CdA) on the colony growth of normal granulocyte-macrophage progenitor cells (CFU-GM) from 15 hematologically healthy donors as well as on CFU-GM from 15 chronic myelogenous leukemia (CML) patients in semisolid cultures in vitro. dFdC and 2-CdA were used either separately or in the following combinations of concentrations: (1) 0.25 nM of dFdC and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Individual publications concern the damage of skin cells and the mucous membrane that was brought about by cladribine (Chubar and Bennett 2003; Rossini et al 2004). Moreover, several publications also described the cytotoxic activity of cladribine on stem cells (Chow et al 2002; Lech-Marańda et al 2000; Petzer et al 1991). In a study on the impact of cytostatic drugs on cells at various stages of maturity, Chow et al showed that cladribine induces apoptosis in CD34 + /CD38 + progenitor cells (Chow et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual publications concern the damage of skin cells and the mucous membrane that was brought about by cladribine (Chubar and Bennett 2003; Rossini et al 2004). Moreover, several publications also described the cytotoxic activity of cladribine on stem cells (Chow et al 2002; Lech-Marańda et al 2000; Petzer et al 1991). In a study on the impact of cytostatic drugs on cells at various stages of maturity, Chow et al showed that cladribine induces apoptosis in CD34 + /CD38 + progenitor cells (Chow et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In a study on the impact of cytostatic drugs on cells at various stages of maturity, Chow et al showed that cladribine induces apoptosis in CD34 + /CD38 + progenitor cells (Chow et al 2002). Lech-Marańda et al observed the inhibition of granulocyte–macrophage progenitor cell growth, and Petzer et al observed the inhibition of T lymphocyte colony forming cells subject to cladribine (Lech-Marańda et al 2000; Petzer et al 1991). …”
Section: Discussionmentioning
confidence: 99%
“…[6,7] These nucleoside analogs are transported into cells mainly through ENTs. To investigate whether imatinib-resistant cells showed reduced sensitivity to gemcitabine (structure shown in Figure 3a), we incubated 32Dp185 and 32Dp185 STI-R cells with 1 μM gemcitabine for 12 hours and performed MTT assays.…”
Section: Imatinib-resistant Cells Are Less Sensitive To Nucleoside Anmentioning
confidence: 99%
“…Current treatment approaches include the combination of treatments using imatinib and compounds such as interferon-α (IFN-α), hemoharringtonine (HHT) and nucleoside analogs such as cytarabine and gemcitabine. [5][6][7][8] Mammalian equilibrative nucleoside transporters (ENTs) are facilitative transporters broadly selective for pyrimidine and purine nucleosides and are essential for the modulation of nucleoside concentration and nucleoside analog availability. Uptake of clinically important nucleoside analogs (e.g., gemcitabine, capecitabine, cytarabine (ara-C)) is mediated primarily by Equilibrative Nucleoside Transporter 1 (hENT1) in human cells.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31] In vitro cytotoxicity data suggest that gemcitabine has significant activity in acute leukemias. [32][33][34] Furthermore, in clinical studies, either alone, [35][36][37][38] or in combination with other agents, 39,40 gemcitabine has activity against human leukemias.…”
Section: Introductionmentioning
confidence: 99%